Synchronous multiple primary colorectal cancer in patients with extraintestinal malignancies - V. V. Podolskiy; E. A. Podolskaya (Сибирский онкологический журнал)
Introduction. The incidence of colorectal cancer (CRC) is steadily increasing in Russia. Patients with cancers of extra-intestinal malignancies are at increased risk of developing CRC. However, currently, there is no a science-based screening system for synchronous primary-multiple CRC among this group of patients. The aim of the study was to analyze features of synchronous CRC among patients with extra-intestinal malignancies. Material and Methods. The medical records of 53 cancer patients registered at the Kursk Oncology Research and Clinical Center named after G.E. Ostroverkhov were analyzed. The inclusion criteria were: the presence of histologically verified newly diagnosed cancer of extra-intestinal location, detection and histological verification of CRC between 2018 and 2022, and the interval between the detection of malignancies of more than 6 months. The decision to conduct an additional examination was made on the basis of complaints of the patients, medical history, physical examination and diagnostic imaging findings. The decision of complex examination was based on complaints, anamnesis and physical data. Results. Among patients with synchronous multiple primary CRC, there were more men (60.4 %) than women. The median age of the patients was 67 years. The risk group for synchronous multiple primary CRC included patients with urological, gynecological, skin, gastric, breast and lung cancers. Examination of the colon in patients with urological, gynecological, skin, gastric and lung cancers (p <0.05) resulted in the detection of synchronous stage I CRC in the distal colon within a month after histologically verified extra-intestinal malignancies in 50.9 % of cases (p<0.05). Conclusion. We recommend the following examination protocol: all primary patients with urological, gynecological, skin, gastric and lung cancers should undergo animmunochemical quantitative fecal occult blood tests no later than 7 days after verification of an extra-intestinal cancer. Such strategy will allow timely detection of multiple primary synchronous CRC.